Perfil da produção de sementes de soja nas diferentes regiões de atuação da Cooperativa Regional Alfa SC - Frozza, Rodrigo (2010)
The market for soybeans has been very demanding and competitive; making the companies entered this market to undergo periodic changes seeking higher quality products, better efficiency of production processes, and not forgetting the products required by the market and marketing. In this light, this paper aims to study seed quality, germination considering the assessment was made as a percentage and in five classes, total quantity produced, evolution of production and marketing of four cultivars of soybean seed produced by Cooperalfa in municipalities of Canoinhas, Chapecó and Xanxerê during the growing seasons of 2005/2006 to 2008/09. Data analysis indicates that the cooperative has difficulty matching the amount of seed to be produced, but it can be said that the seed crop produced in 2005/06 to 2008/09 have excellent germination, and the Xanxerê s plant produces seeds with superior physiological quality, and more than 80% of seed lots regardless of place of production and years of cultivation have more than 85% germination being recommended to invest in cooperative marketing analysis, trends, innovations and industry assessments new cultivars.